EL MESIANISMO EN EL PENSAMIENTO DE WALTER BENJAMIN - Frajman Lerner, Mauricio (2023)
Walter Benjamin is very well recognized as an art critic. His way of thinking was brilliantly described by Michael Lowy as”very distant from all other current ideas and as the crossing of two roads”. Those two roads are: the dialectical materialism with a lot of influence of Bertolt Brecht and the Jewish messianism influenced by his great friend Gershom Sholem.Benjamin was torn away from the social forces that surrounded him and this is why he was considered a Jew between the Germans and a German among the Jews, a Communist between the Zionists and a Zionist among the Communists. This allowed him to hold a constant critical position, where art becomes the most important issue among the workers conscience, being the artistic technical reproduction as film and photography, the breaking of the aura of the unique art product, the one that characterized fascist art for the masses. This massive reproduction of art revolves sensations and moves the people towards personal redemption (tikun) as well as to social redemption (social revolution).This processwould be equivalent to the messianic times, the arrival of the messiah, the moment of return to the lost paradise, a peaceful place where the human being will return to his unique condition, the image of the creator, where there are neither oppressors nor oppressed people.